IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR PKN - Purbani Pudji Sayekti (EduStream: Jurnal Pendidikan Dasar, 2022)
The use of the picture and picture type cooperative method is expected to increase student activity in the teaching and learning process so that in the teaching and learning process teaching and learning activities do not occur saturation, thus students will be physically, emotionally and intellectually involved which in turn is expected to change the concept of objects taught by the teacher. teachers can be understood by students. This research is based on the following problems: (a) How is the improvement of student achievement with the application of the picture and picture cooperative learning method? (b) How is the effect of the picture and picture cooperative learning method on students' learning motivation?. While the objectives of this research are: (a) Want to know the increase in student achievement after the implementation of the picture and picture model cooperative learning method (b) Want to know the effect of student learning motivation after the picture and picture model cooperative learning method is applied. This study uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The targets of this study were students of class II-c SDN Dukuh Menanggal I/424 Surabaya. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement has increased from cycle I (80.56%) to cycle II (91.67%). SDN Dukuh Menanggal I/424 Surabaya and this learning model can be used as an alternative thematic learning, especially the Civics subject.